Enhanced sarcoplasmic reticulum Ca2+ leak and increased Na+-Ca2+ exchanger function underlie delayed afterdepolarizations in patients with chronic atrial fibrillation - Voigt, Niels; Sun, Qiang; Wieland, Thomas; Dobrev, Dobromir (Circulation, 2012)
Background: Delayed afterdepolarizations (DADs) carried by Na+-Ca2+-exchange current (INCX) in response to sarcoplasmic reticulum (SR) Ca2+ leak can promote atrial fibrillation (AF). The mechanisms leading to delayed afterdepolarizations in AF patients have not been defined. Methods and Results: Protein levels (Western blot), membrane currents and action potentials (patch clamp), and [Ca2+]i (Fluo-3) were measured in right atrial samples from 76 sinus rhythm (control) and 72 chronic AF (cAF) patients. Diastolic [Ca2+]i and SR Ca2+ content (integrated INCX during caffeine-induced Ca2+ transient) were unchanged, whereas diastolic SR Ca2+ leak, estimated by blocking ryanodine receptors (RyR2) with tetracaine, was ≈50% higher in cAF versus control. Single-channel recordings from atrial RyR2 reconstituted into lipid bilayers revealed enhanced open probability in cAF samples, providing a molecular basis for increased SR Ca2+ leak. Calmodulin expression (60%), Ca2+/calmodulin-dependent protein kinase-II (CaMKII) a...